List of individuals enquired into - Cornish, F.
1902-01-01 1902 1900s 2 pages Spong — Harry. Comp 181 Morley Avenue, Noel Park, Green Lanes. Key — Fredk. Cooper, 17 Pelham Rd Wood Green, Green Lanes Smith — Lily. F. Lab 13 Brook Rd Wood Green, Green Lanes Phipps — Thos. Bricklayer 49 Coburg Rd. „ „ „ „ Leonard — Crowe. Lab 2 Stanley Rd New Southgate Abbey — Edward. Gard. 24 Lower Park Road „ „ Hatshood Alice Servt 59 Victoria Rd. Stroud Green Roots Herbert Farrier 12 Harringay Rd West Green Wright — Geo. F. Lab. 13 Willow Walk „ „ Mead — Willm Lab 16 Milton Rd. „ „ The above should be Collenpeek not Peck Hall Christine F Carman 112 Morley Avenue Noel Park Rowley, Herbert, F Carpenter, 2 Brampton Rd. West Green Spinks, Alfred, Painter 70 Avondale Rd. „ „ Lush, Susan. H. Carman 37 Park Rd „ „ 378/IMSW/A/1/6/8